Helminth diversity of nutria (Myocastor coypus) across the Morava basin in the Czech Republic - Michal Benovics; Eva Nosková; Anna Klimešová; Lucie Škorpíková; Ema Jaššová; Jakub Drimaj; Jan Slováček; Ondřej Mikulka (Parasitology)
The nutria was introduced to Europe from South America and kept for the fur industry. This semiaquatic rodent became a well-established species in the Czech Republic; however, it still poses a significant threat to the native fauna, not only as a natural competitor but also as a vector of non-indigenous parasites. Our research aimed to investigate the diversity of endoparasitic helminths in nutria, with a particular focus on assessing the risk posed by helminth species with zoonotic potential. A total of 46 nutria cadavers were collected at 8 locations in the Morava River basin and examined using standard parasitological post-mortem procedures. Additionally, coprological and molecular methods were used to identify the parasites. The presence of 6 helminth species was revealed. The highest prevalence was observed for Strongyloides myopotami (78.3%) and Trichuris myocastoris (37.0%), both of which are host-specific nematodes of nutria. Only 2 trematode taxa were recorded (Echinostoma sp. and a representative of the family Psilostomidae). The presence of alveolar hydatid cysts of Echinococcus multilocularis in the livers of 5 nutria specimens was also recorded. Herein, we provide novel molecular data for each parasite species collected, which is valuable for future phylogenetic analyses. Our findings also demonstrate that nutria in the Czech Republic serve as a carrier of helminths with zoonotic potential, particularly E. multilocularis and S. myopotami. Although the nutria is a relatively new species in local fauna, its synanthropic behaviour raises concerns about potential threats to human health, underscoring the importance of exercising caution when handling these animals.